Pendampingan dan Penguatan UMKM Desa Tambong melalui Branding, Strategi Pemasaran dan Pencatatan Laporan Keuangan Sederhana dalam Menghadapi Era New Normal - Alfiyah, Nurul; Ratri, Indira Nuansa (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The Covid-19 pandemic has given rise to a new world order called the new normal era. This new arrangement raises a number of new business competitions, especially the use of digital-based marketing media. This challenge is felt especially for Small and Medium Enterprise (SME) in Tambong village who still have very little knowledge about how to do marketing, build a brand image, financial management and knowledge of information technology. The implementation of service activities begins with initial coordination activities with the Tambong village, visits to several Small and Medium Enterprise (SME) and then the preparation and implementation of work programs. The implementation includes brand image socialization, packaging and digital marketing, crystallization training for herbal medicine and financial management training for 2 pilot Small and Medium Enterprise (SME), namely Small and Medium Enterprise (SME) that produce hijab with the kiya hijab label and Small and Medium Enterprise (SME) of traditional herbal medicine. This community service activity has benefits for partners. The dissemination of brand image and packaging provided motivated partners to be able to further develop and advance their business and be able to compete with other similar products. Herbal medicine crystallization training expands product marketing and also product shelf life will be more durable with more attractive product packaging. The financial management training provided motivates Partners to be able to manage finances neatly and consistently even though it's still simple